Postharvest Properties of Ultra-Late Maturing Peach Cultivars and Their Attributions to Melting Flesh (M) Locus: Re-evaluation of M Locus in Association With Flesh Texture - Nakano, Ryohei; Kawai, Takashi; Fukamatsu, Yosuke; Akita, Kagari; Watanabe, Sakine; Asano, Takahiro; Takata, Daisuke; Sato, Mamoru; Fukuda, Fumio; Ushijima, Koichiro (Frontiers in Plant Science, 2020)
The postharvest properties of two ultra-late maturing peach cultivars, ‘Tobihaku’ (TH) and ‘Daijumitsuto’ (DJ), were investigated. Fruit were harvested at commercial maturity and held at 25°C. TH exhibited the characteristics of normal melting flesh (MF) peach, including rapid fruit softening associated with substantial level of endogenous ethylene production In contrast, DJ did not soften at all during three-week experimental period even though substantial ethylene production was observed. Fruit of TH and DJ were treated with 5000 ppm of propylene, an ethylene analog, continuously for seven days. TH softened rapidly whereas DJ maintained high flesh firmness in spite of an increase in endogenous ethylene production, suggesting that DJ but not TH lacked the ability to be softened in response to endogenous and exogenous ethylene/propylene. DNA-seq analysis showed that tandem endo-polygalacturonase (endoPG) genes located at melting flesh (M) locus, Pp-endoPGM (PGM) and Pp-endoPGF (PGF), were deleted in DJ. The endoPG genes at M locus are known to control flesh texture of peach fruit, and it was suggested that the non-softening property of DJ is due to the lack of endoPG genes. On the other hand, TH possessed an unidentified M haplotype that is involved in determination of MF phenotype. Structural identification of the unknown M haplotype, designated as M0, through comparison with previously reported M haplotypes revealed distinct differences between PGM on M0 haplotype (PGM-M0) and PGM on other haplotypes (PGM-M1). Peach M haplotypes were classified into four main haplotypes: M0 with PGM-M0; M1 with both PGM-M1 and PGF; M2 with PGM-M1; and M3 lacking both PGM and PGF. Re-evaluation of M locus in association with MF/non-melting flesh (NMF) phenotypes in more than 400 accessions by using whole genome shotgun sequencing data on database and/or by PCR genotyping demonstrated that M0 haplotype was the common haplotype in MF accessions, and M0 and M1 haplotypes were dominant over M2 and M3 haplotypes and co-dominantly determined the MF trait. It was also assumed on the basis of structural comparison of M haplotypes among Prunus species that the ancestral haplotype of M0 diverged from those of the other haplotypes before the speciation of Prunus persica.